Iron deficiency anemia in the emergency department: over-utilization of red blood cell transfusion and infrequent use of iron supplementation. Issue 3 (7th November 2016) - Spradbrow, Jordan; Lin, Yulia; Shelton, Dominick; Callum, Jeannie
Abstract: Objectives: Three are no clinical practice guidelines that specifically address the management of patients with iron deficiency anemia (IDA) in the emergency department (ED). The goal of this study was to describe the characteristics of IDA patients who present to the ED, documentation of IDA by emergency physicians, utilization of iron supplementation, and the appropriateness of red blood cell (RBC) transfusions ordered in the ED. Methods: A retrospective medical chart review was performed of IDA patients who visited the ED of a large tertiary center over a three-month period. Appropriateness of RBC transfusion was determined using a novel algorithm developed by our institution. Results: Over the study period, there was a 0.3% (49/14, 394) prevalence of IDA in the ED. In thirty (30/49; 61%) patients, IDA was documented by an emergency physician. RBC transfusions were administered to 19 patients; 10 transfusions (53%) were appropriate, 3 (16%) were appropriate for indication, but more than the required number of units were ordered, and 6 (32%) were inappropriate. Of the patients discharged, one (1/25; 4%) patient received intravenous iron in the ED and 6 of the 11 patients (55%) that were not already taking oral iron received a prescription at discharge from the ED. Conclusions: This assessment demonstrated that management of IDA patients presenting to the ED may represent an important knowledge-to-practice gap. It revealed that RBC transfusion may be over-utilized and could be replaced by safer, lower-cost alternatives such as intravenous and oral iron. Guidelines for management of IDA in the ED may be necessary to achieve consistent IDA management and avoid inappropriate use of RBC transfusion. RÉSUMÉ: Objectif: Il n'existe pas de guide de pratique clinique portant en particulier sur la prise en charge de l'anémie ferriprive (AF) au service des urgences (SU). L'étude décrite ici avait pour but de caractériser les patients atteints d'AF au SU, les notes consignées au dossier par les médecins d'urgence sur l'AF, l'utilisation de la supplémentation martiale et la pertinence des transfusions de culots globulaires (CG) au SU. Méthode: Il s'agit d'un examen rétrospectif de dossiers médicaux de patients atteints d'AF, qui ont consulté un médecin au SU d'un important centre hospitalier de soins tertiaires sur une période de trois mois. La pertinence des transfusions de CG a été déterminée à l'aide d'un nouvel algorithme élaboré dans l'établissement des auteurs. Résultats: Durant la période à l'étude, le taux de prévalence de l'AF au SU s'est élevé à 0, 3 % (49/14 394). Dans 30 (30/49; 61 %) cas, l'AF a été consignée par un médecin d'urgence. Dix-neuf patients ont reçu des transfusions de CG : chez 10 (53 %) d'entre eux, les transfusions étaient appropriées; chez 3 (16 %) autres, les transfusions étaient appropriées compte tenu de l'indication, mais on a demandé un nombre de culots plus élevé que ce qui était nécessaire; et chez les 6 (32 %) derniers, les transfusions étaient inappropriées. Parmi les patients qui ont obtenu leur congé, 1 (1/25; 4 %) a reçu du fer par voie intraveineuse au SU et, sur les 11 qui ne prenaient pas déjà de fer par voie orale, 6 (55 %) ont reçu une ordonnance au moment du congé du SU. Conclusions: D'après l'étude, il existerait un important écart entre les connaissances et la pratique relativement à la prise en charge de l'AF au SU. En effet, l'examen a révélé une surutilisation possible des transfusions de CG, traitement qui pourrait être remplacé par des solutions de rechange plus sûres et moins coûteuses telles que l'administration de fer par voie intraveineuse ou par voie orale. Il serait donc justifié d'élaborer un guide de pratique clinique sur la prise en charge de l'AF au SU afin d'assurer une prise en charge uniforme de l'affection et d'éviter l'utilisation inappropriée des transfusions de CG.